An inquiry into well-being and destitution - Partha Dasgupta (Oxford Univ, 1995)
This volume is a seminal work dealing comprehensively with the problem of poverty. It is an analytical and an empirical inquiry into human well-being and the phenomenon of destitution. A central concern of the author has been to reconcile theoretical considerations with the empirical evidence that has been obtained in the several disciplines this work encompasses: anthropology, demography, ecology, economics, epidemiology, geography, moral and political philosophy, and the environmental , nutrition and political sciences